Morphological redescription of immature and adult stages of Culex (Culex) acharistus Root (Diptera: Culicidae) - Laurito, Magdalena (2009)
Culex (Culex) acharistus Root is redescribed in the adult, pupal and larval stages. The male genitalia, pupa, and fourthinstar larvae are illustrated. The paper includes available information on the distribution, bionomics and taxonomy of the species.